1974
DOI: 10.1159/000197553
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Curve to Secretin on Gastric Mucus Secretion in Conscious Cats

Abstract: The effect of secretin on gastric mucus was studied simultaneously with acid and pepsin secretions in three conscious cats with gastric fistula and Heidenhain pouch. The glycoprotein fraction of mucus was estimated by fucose and galactose concentration and the polysaccharide fraction by uronic acid concentration in homogenized gastricjuice. Secretin produced stimulation of both fractions which persisted during continuous infusion and was proportional to the doses. However, this action was greater on the polysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
1

Year Published

1978
1978
2000
2000

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 7 publications
3
11
1
Order By: Relevance
“…In agreement with previous studies, we found that secretin induced an increase in the output of major carbohydrate components, represent ing glycoprotein fraction of gastric mucus and also in the output of uronic acid, considered a representative of the polysaccharide fraction of gastric mucus (9). This study agrees with our previous experiment, concerned with the com position of gastric mucus, secreted by the iso lated mammalian stomach perfused extracorporeally (11).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with previous studies, we found that secretin induced an increase in the output of major carbohydrate components, represent ing glycoprotein fraction of gastric mucus and also in the output of uronic acid, considered a representative of the polysaccharide fraction of gastric mucus (9). This study agrees with our previous experiment, concerned with the com position of gastric mucus, secreted by the iso lated mammalian stomach perfused extracorporeally (11).…”
Section: Discussionsupporting
confidence: 93%
“…Secretin was found previously to stimulate gastric mucus secretion in cats (8,9) and man (7), and in Brunner canine pouches (25). Vague (9) estimated glycoprotein fractions of mucus by fucose and galactose concentration and the polysaccharide fraction by uronic acid concen tration in homogenized gastric juice.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Estimation of luminal mucus in gastric washings has been used extensively as an index of secretion. For example, pentagastrin, histamine and prostaglandins have been reported to increase luminal glycoproteins (25)(26)(27)(28)(29). However, various phenomena may induce variation in soluble mucus -a shift of adherent glycoproteins to soluble mucus, an increased rate of mucus secretion of adherent glycoproteins or an increased breakdown of mucus by excessive mucolytic activity of pepsin.…”
Section: Discussionmentioning
confidence: 99%